Hypothesis: Musculin is a hormone secreted by skeletal muscle, the body’s largest endocrine organ - Engler, Dennis (Acta Biomedica Atenei Parmensis, 2007)
Recent studies indicate that skeletal muscle may act as an endocrine organ by secreting interleukin-6 (IL-6) into the systemic circulation. From an analysis of the actions of IL-6 and of additional literature, we postulate that skeletal muscle also secretes an unidentified hormone, which we have named Musculin (Latin: musculus = muscle), which acts on the pancreatic b-cell to restrain the size of the b-cell mass and to tonically inhibit insulin secretion and biosynthesis. It is suggested that the amount of Musculin secreted is determined by, and is positively correlated with, the prevailing insulin sensitivity of skeletal muscle, thereby accounting for the hyperinsulinemia that occurs in insulin resistant disorders such as type 2 diabetes mellitus, obesity, and the polycystic ovary syndrome. In addition, it is postulated that Musculin acts on the hypothalamus (arcuate nucleus, dorsomedial hypothalamic nucleus) to co-ordinate the neuroendocrine and appetite responses to exercise. However, the possibilities that Musculin may act on additional central nervous system sites and that an additional hormone(s) may be responsible for these actions are not excluded. It is suggested that a search be made for Musculin, since analogues of such a substance may be of therapeutic benefit in the treatment of the current global diabetes and obesity epidemic.